2014
DOI: 10.1002/ajoc.201402098
|View full text |Cite
|
Sign up to set email alerts
|

Application of Regio‐ and Stereoselective Functional Group Transformations of Chiral Aziridine‐2‐carboxylates

Abstract: Chiral aziridine-2-carboxylates have two important functional groups, the carboxylate group and aziridine ring, that are useful for synthetic purposes. As both (2R)-and (2S)-aziridine-2-carboxylates were commercialized in optically pure forms, we have studied to extend their synthetic utilities for the construction of various nitrogen-containing molecules. The C2 ester group can be transformed into aldehydes, alcohols, amides, ketones, b-ketoesters, and amines bearing diverse substituents with defined stereoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…The regiochemistry of analogous 1‐azoniabicyclo[3.1.0]hexane tosylate ( 7 ) was extensively studied by using DFT calculations to draw the conclusion that the selection of the reaction pathway was governed by the kinetic and thermodynamic properties of each reaction, depending on the characteristics of the nucleophile . Unless the reaction was equilibrated with the aziridinium ion, all of the reactions were dominated by the kinetic pathways, that is, which ring formed first between the piperidine and azepane with a lower transition state energy …”
Section: Resultsmentioning
confidence: 99%
“…The regiochemistry of analogous 1‐azoniabicyclo[3.1.0]hexane tosylate ( 7 ) was extensively studied by using DFT calculations to draw the conclusion that the selection of the reaction pathway was governed by the kinetic and thermodynamic properties of each reaction, depending on the characteristics of the nucleophile . Unless the reaction was equilibrated with the aziridinium ion, all of the reactions were dominated by the kinetic pathways, that is, which ring formed first between the piperidine and azepane with a lower transition state energy …”
Section: Resultsmentioning
confidence: 99%
“…Evidently, the initially generated aziridinium ion 19 underwent a nucleophilic opening reaction with molecule of water from the sterically less hindered si ‐face of the intermediate at the more substituted carbon. Analogous to the acid‐catalyzed ring opening of the unsymmetrical epoxide, water, as a nucleophile, attacks at the more substituted carbon, which develops a more positive character during the reaction . The spiro‐hemiaminal 20 was then subjected to the standard reductive debenzylation under an atmosphere of H 2 (1 atm) in the presence of Pd/C in MeOH.…”
Section: Resultsmentioning
confidence: 99%
“…Enantiopure aziridine‐2‐carboxylates have been used as chiral starting materials in the asymmetric syntheses of a series of nitrogen‐containing cyclic and acyclic molecules, including biologically important amino acids, amino alcohols, and diamines through transformation of the carboxylate group and ring opening or expansion . We have previously demonstrated that the aziridine carboxylate can be readily converted into a variety of stereochemically well‐defined functional groups . We have also shown that the aziridine ring can be selectively opened in the sense of both regio‐ and stereochemistry, depending on the substrates, the nucleophiles used, as well as activating groups .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Therefore, the transformation of the carboxylate group is feasible withoutt he concomitantb reakage of the ring under relativelyh arsh reaction conditions, unless exposed to acid. [5,6] Herein, we describe the stereoselective epoxidation of 3-(aziridin-2-yl)acrylaldehyde (1)t oi ntroducea ne poxide next to the aziridine and afford 3-(aziridin-2-yl)oxirane-2-carbaldehyde( 2), which is av aluablec ompound with versatile applicationsc ontaining three consecutive functional groupss uch as aziridine, epoxide and aldehyde( Scheme 1). [5,6] Herein, we describe the stereoselective epoxidation of 3-(aziridin-2-yl)acrylaldehyde (1)t oi ntroducea ne poxide next to the aziridine and afford 3-(aziridin-2-yl)oxirane-2-carbaldehyde( 2), which is av aluablec ompound with versatile applicationsc ontaining three consecutive functional groupss uch as aziridine, epoxide and aldehyde( Scheme 1).…”
mentioning
confidence: 99%
“…In the last two decades, we have studied chiral aziridines startingf rom enantiopure (2R)-or (2S)-[(1R)-phenylethyl]-aziridine-2-carboxylate [5] and the construction of various nitrogencontaining molecules focusingo nt wo important synthetic strategies, that is, the functional group transformation of carboxylates and the ring openingo fa ziridines. [6] (2R)-or (2S)-[(1R)-phenylethyl]aziridine-2-carboxylate are non-activated aziridines bearing electron-donating substituents at the ring, in which the nitrogen is stabilized and is inert to directr ingopeningr eactions with various nucleophiles. [7] Therefore, the transformation of the carboxylate group is feasible withoutt he concomitantb reakage of the ring under relativelyh arsh reaction conditions, unless exposed to acid.…”
mentioning
confidence: 99%